ANALISIS PERUBAHAN BENTUK TOPOGRAFI DASAR LAUT SELAT BANGKA (Studi Kasus : Selat Bangka, Perbatasan Pulau Sumatera dan Pulau Bangka) - , ELISA MAIYENTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Bangka Strait is one of area of tin exploitation in Indonesia. Bangka Strait lies between Sumatera Island and Bangka Island. Establishment of Bangka Belitung province on December 21, 2000 resulted in the loosening of regulations exploitation of tin in Bangka Strait. It caused increasing mining activities ranging from legal to illegal. Those causes damage to the structure of the seabed topography Bangka Strait. Presentation of the information is necessary to get the information of depth changes and output volume values caused by offshore tin mining in Bangka Strait before and after the year 2000. The method used in this research is by analyze changes using depth differences and output volume values which is resulted by comparing first epoch, in 1996 with the second epoch, in 2012. Reduced data acquisition is done with the correction of the raw data to draft transducer and to vertical datum. Acquisition of vectical datum is obtained from tidal data processing to get major tidal harmonic constants. Major tidal harmonic constants used to obtain the value of vertical datum and tidal type to obtain bathymetric reduced data. Analysis using software ArcGIS10 changes include making bathymetric maps, making cross sections, volume computations, and depth changes. The results obtained from this study is the change in the form of seabed topography from 1996 until 2012. Changes of seabed topography of Bangka Strait is shown by bathymetric maps and graph sections of epoch in 1996 and 2012. The change occur in the form of additional depth of -21.5 meters depth into -21.5661 meter amounted to -0.06613 meters as the lowest depth of change and of -7 meters to -33.852 meters amounted to -26.852 meters as the highest depth. The output volumes occur in the form of cut volume of 797790619 cubic meters in area of 91956541.94 square meters and fill volume of 3733011.406 cubic meters in area of 2603376.187 square meters